Distribution of Mast Cells in The Small Intestine in Different Periods of Pregnancy in Rats - USLU, Sema; TATAR, Musa (Cumhuriyet University, 2022)
The gastrointestinal tract has different characteristics. The gastrointestinal tract is affected by the enlarging uterus as pregnancy progresses. The enlargement of the uterus changes the digestive organs, especially the metabolism of the stomach and intestines. Anatomical changes produce acute abdominal changes. In addition to the mechanical effects caused by the growing uterus, high progesterone levels cause delayed gastric emptying and increased gastrointestinal transit time. Stomach and intestinal motility are also affected, resulting in lower transit times. Mast cells are cells that are activated and show degranulation under all kinds of stress conditions. These cells are considered to be cells that play an important role in the physiological and pathological responses of the immune system by showing both proinflammatory and immunosuppressive functions. Maternal malnutrition adversely induces fetal bowel development and function through the maternal intestinal barrier, intestinal content, structure, and peripheral circulation. In this study, samples were taken from the small intestine in 3 different trimesters of pregnancy. Tissue samples taken from duodenum, jejunum and ileum were fixed in Carnoy solution for 12 hours. Paraffin blocks were prepared after tissue follow-up without washing. Paraffin blocks were formed from the samples and 5-6 µ thick sections were taken and stained with 0.5% Toluidine Blue to determine the distribution of mast cell number. After staining, the distribution of mast cells in the lamina propria + submucosa and tunica serosa layers was examined. It was determined that mast cells changed numerically in the duodenum, jejunum and ileum in the small intestine according to the layers and according to the gestational periods. It is thought that this study will contribute to the literature on this subject.
Keywords: 3. Good health